Engaging Diverse Audiences: The Role of Community Radio in Rural Climate Change Knowledge Translation - Abdul-Rahim Abdulai; Vincent Kuuteryiri Chireh; Roza Tchoukaleyska (The University of Alabama, 2021)
Community radio is an important form of knowledge dissemination, especially in rural areas where it can create opportunities for a geographically spread-out audience to engage in local debates. Through this article, we reflect on the community-building function of radio and consider how it can be mobilized to support climate change knowledge transfer in rural communities. Our reflections draw on the use of community radio during the Gros Morne Climate Change Symposium, an event that brought together researchers, practitioners, and community members to discuss coastal climate change adaptation in Newfoundland and Labrador, Canada. We consider the history of radio in Canada, its role in rural communities, and review experiences with radio-focused knowledge dissemination in other locations to frame our own discussion of the topic. Through reflection, each of the co-authors highlights their understanding of the role of community radio at the symposium and argue for the continuing relevance of radio in an era when digital communications are more common. We conclude by arguing that community radio can strengthen place-based identities by creating a distinct forum for engagement and is therefore an important tool for climate change knowledge transfer.